Factors affecting the motivation and intention to become an entrepreneur among business university students. (2018) - Raza, Syed Ali; Qazi, Wasim; Shah, Nida
The purpose of this study is to explore how the variables of the theory of planned behaviour and motivation and ability model affect the intention to become an entrepreneur among business university students. For this purpose, data were collected from 267 students of different business schools of Pakistan. PLS-SEM was used as a statistical tool to analyse the data. The result revealed that the variables, i.e., Subjective norm, opportunity, attitude, perceived behavioural control has a positive and significant effect on the motivation, and motivation also has a significant positive effect on the students' intention to become an entrepreneur, however, ability has a positive but insignificant on motivation. From this study it can be concluded that the only financial resources are not enough to start a business, behavioural factors also play the critical role. This research gives valuable insights for the policy implications.